2011
DOI: 10.1136/jnis.2010.004390
|View full text |Cite
|
Sign up to set email alerts
|

The impact of coil shape design on angiographic occlusion, packing density and coil mass uniformity in aneurysm embolization: an in vitro study

Abstract: Objective To investigate the impact of coil design on the distribution of the coil mass in a controlled in vitro experiment. A secondary objective was to study the relationship between angiographic occlusion, packing density and coil mass uniformity. Methods Seven silicon side wall aneurysm models were embolized in each arm with a different coil design under fluoroscopic guidance. Packing density calculations and scoring of the angiographic occlusion were made. The models were embedded in epoxy and sectioned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 15 publications
(23 reference statements)
0
21
0
Order By: Relevance
“…However, when hydrocoil represented >75% or when it was the final coil placed, the rate of recurrence was significantly lower (p=0.035 and p=0.047, respectively) 11. Indeed, a more uniform hydrogel coil distribution in the aneurysm sac and, in particular, in the aneurysm neck, may be more relevant to achieving a better occlusion rates than PD as demonstrated in some in vitro studies 12 13…”
Section: Discussionmentioning
confidence: 99%
“…However, when hydrocoil represented >75% or when it was the final coil placed, the rate of recurrence was significantly lower (p=0.035 and p=0.047, respectively) 11. Indeed, a more uniform hydrogel coil distribution in the aneurysm sac and, in particular, in the aneurysm neck, may be more relevant to achieving a better occlusion rates than PD as demonstrated in some in vitro studies 12 13…”
Section: Discussionmentioning
confidence: 99%
“…In-slice coil density has recently been calculated to assess coil distribution in a similar way but in silicone coiled aneurysm models 26. In this study the authors used slices of the aneurysm dome and neck that were partitioned in angular regions to assess coil distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro data by Mehra et al 27 showed superior regularity in distribution within a volume relative to helical primary wind designs from the same manufacturer.…”
Section: Different Primary Windsmentioning
confidence: 98%